Analisis Kinerja Mekanisme Routing Flooding dan Convergecast Pada Wireless Sensor Network - Kharisma Fadillah; Heru Nurwarsito (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Wireless Sensor Network (WSN) is a wireless sensor network that has a specific purpose, including use for monitoring. To find out the transferred data packets and the total number of data packets lost requires a routing protocol that is tasked with determining the shortest path from the source node to the destination node. use of power in the WSN network, where the results obtained routing gossiping are more efficient in terms of energy. From previous research, the researcher took the idea that convergecast routing has one of the same advantages of flooding routing, namely the same as having the best performance in data transmission. This research analyzes the routing protocol algorithm flooding and convergecast which aims to assess the performance of the routing performance based on latency, backoff time, power consumption, as well as to analyze the optimum type of routing protocol in a wireless sensor network. Topology design uses 5 kinds of nodes, namely 7, 14, 21, 28, and 35 nodes. Testing is done with parameters of latency, backoff, activity durations, and power consumption. The result of the activity durations parameter is 13 ms, then latency is below 0.005 ms, while for routing flooding it has a value that is almost the same as the convergecast at the end of the node for backoff parameters (3.1 ms convergecast & 3.2 ms flooding) and power consumption (56.3 mW second routing)